An FDTD Investigation of Compact and Low-Voltage Waveguide-Integrated Plasmonic Ge/SiGe Multiple Quantum Wells Photodetectors - Saranisorn Srikam; Worawat Traiwattanapong; Pichet Limsuwan; Papichaya Chaisakul (My University, 2022)
We report on 3-D FDTD simulation of waveguide-integrated plasmonic Ge/SiGe MQWs photodetectors. Despite several significant works on Ge/SiGe MQW optical modulators, Ge/SiGe MQW photodetectors still show improvable performance, limiting the potential to employ them for both optical modulation and detection. In this paper, we investigate the use of plasmonic concept to enhance electromagnetic field confinement inside the Ge/SiGe MQWs absorbing region with a view to having a compact and low-voltage waveguide-integrated Ge/SiGe MQWs photodetectors. Optical responsivities in term of applied electric fields, device dimensions of width and length, optical bandwidth, fabrication misalignment, and number of QWs periods are taken into account. The investigation shows that using plasmonic enhancement, a waveguide-integrated Ge/SiGe MQWs photodetector that is as short as 5 μm could be obtained with comparable responsivity and bias voltage values to some of the state-of-the-art bulk Ge-based devices, increasing the potential usage of Ge/SiGe MQWs for both optical modulation and detection in low-energy optical interconnects.
Keywords: Waveguide; Photonic and Optical Devices